ENVIRONMENTAL ASSESSMENT OF PASTURE LAND QUALITY - Omarova, A.; Turguldinova, S. (Scientific Journal of Pedagogy and Economics, 2020)
In the Message of the President to the people of the Republic of Kazakhstan N. A. Nazarbayev "the Third modernization of Kazakhstan: global from January 2017, it is said "the agro-industrial complex of Kazakhstan has a promising future", "we will help to be one of the largest producers of agricultural export products" [1]. Kazakhstan ranks sixth in the world in terms of its grass resources. Pasture land is 189.0 million hectares, historically being the driving force in the country’s economy, as a source of feed resources for the development of livestock [2]. According to the Agency of the Republic of Kazakhstan, there are 27.1 million hectares of pastures that were shot down in an average and severe degree. In the zonal aspect, the destruction of pasture ecosystems is mostly observed in the flat part, where more than 95% of all downed pastures are located, including the desert and semi – desert zones-16.1 million hectares or 60% of their area. Downed pastures are the main consequence of changing environmental conditions and irrational human economic activity. It is manifested in the loss of valuable forage plant species from the herbage and their replacement with weeds, non-edible and annual species [3,4].